Gateway to doping? Supplement use in the context of preferred competitive situations, doping attitude, beliefs, and norms - Backhouse, S. H.; Whitaker, L.; Petroczi, A. (Scandinavian Journal of Medicine & Science in Sports, 2013)
Nutritional supplement (NS) use is widespread in sport. This study applied an integrated social cognitive approach to examine doping attitudes, beliefs, and self-reported doping use behavior across NS users (n = 96) and nonusers (n = 116). Following ethical approval, 212 competitive athletes (age mean = 21.4, s = 4.5; 137 males) completed self-reported measures of doping-related social cognitions and behaviors, presented in an online format where completion implied consent. Significantly more NS users (22.9%) reported doping compared with nonusers (6.0%; U = 4628.0, P < 0.05). NS users presented significantly more positive attitudes toward doping (U = 3152.0, P < 0.05) and expressed a significantly greater belief that doping is effective (U = 3152.0, P < 0.05). When presented with the scenario that performance-enhancing substances are effective and increase the possibility of winning, NS users were significantly more in favor of competing in situations that allow doping (U = 3504.5, P < 0.05). In sum, doping use is three-and-a-half times more prevalent in NS users compared with nonusers. This finding is accompanied by significant differences in doping attitudes, norms, and beliefs. Thus, this article offers support for the gateway hypothesis; athletes who engage in legal performance enhancement practices appear to embody an "at-risk" group for transition toward doping. Education should be appropriately targeted.